PENDIDIKAN DAN KESETARAAN: IMPLEMENTASINYA PADA SEKOLAH INKLUSI PERSPEKTIF FILSAFAT MANUSIA - April Juwan, Dian Paula; Dwiputri Maharani, Septiana; Siswadi, Gede Agus (Widya Aksara : Jurnal Agama Hindu, 2024)
Inclusive education is being promoted to ensure equal education for all students, regardless of background or special needs. Human philosophy emphasises respect for each person's dignity and potential. Nevertheless, the execution of the notion of inclusive education frequently encounters intricate obstacles. This study examines how human philosophy values and principles might promote equality in inclusive schools. The research methodology employs a qualitative approach, primarily emphasising literature analysis and case studies. The literature analysis will examine inclusive education-related human philosophy principles and theories, while the case studies will examine how inclusive schools use these concepts. This research integrates theoretical and empirical data to better understand the relationship between human philosophy and inclusive education and promote more inclusive and humane educational practices. Inclusive education is an education that supports equality. Because basically, all humans need education as an effort to develop their talents and interests.